(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2016)
Background: Menstruation is one of the natural changes that occur in female in her normal life. Though it is a natural phenomenon, most of the adolescent girls have some wrong beliefs and behavior regarding menstruation. Objective: To assess knowledge on menstruation among adolescence school girls in a selected area of Dhaka City. Methods: A descriptive cross sectional study was conducted among conveniently selected 240 adolescent girls. A pre-tested modified questionnaire was used to get data by face to face interview. Knowledge level was determined by predefined scoring. Results: Mean age of respondents was 15.46 + 1.17 years. Mean monthly family income of respondents was 22500±4256 BDT. Majority of the respondents (88%) did not have knowledge about menstruation before the onset of their menarche. Most of the respondents (88%) were not mentally prepared for the first period. About 5.6% of the respondents felt good or normal during menstruation followed by 51%, 39.4% and 4% had uncomfortable, afraid and disgusting feeling respectively. Majority of the respondents (44%) knew about menstruation from TV. Conclusion: Most of the respondents had poor knowledge/no knowledge about menstruation. Chatt Shi Hosp Med Coll J; Vol.15 (1); Jan 2016; Page 31-34